2019
DOI: 10.1155/2019/2439571
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Having a Late Dinner or Bedtime Snack and Skipping Breakfast with Overweight in Japanese Women

Abstract: Background. We aimed to assess the association of habitually eating in the late evening and skipping breakfast with the prevalence of overweight/obesity. Methods. A total of 19,687 Japanese women, aged 40–74 years, were asked about their height, weight, and habitual eating behaviors such as having a late dinner and a bedtime snack and skipping breakfast, using a self-administered questionnaire. We defined overweight/obesity as body mass index greater than or equal to 25 kg/m2. Results. Among the participants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 31 publications
(28 reference statements)
6
45
0
1
Order By: Relevance
“…A trend of higher risk of LBP associated with higher lifestyle risk score was observed in both sexes (p for trend < 0.001). These results were similar even in subgroup analysis by age (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), and ≥ 60 years) and body mass index (BMI) (< 18.5, 18.5-24.9, and ≥ 25 kg/m 2 ).…”
supporting
confidence: 66%
See 2 more Smart Citations
“…A trend of higher risk of LBP associated with higher lifestyle risk score was observed in both sexes (p for trend < 0.001). These results were similar even in subgroup analysis by age (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), and ≥ 60 years) and body mass index (BMI) (< 18.5, 18.5-24.9, and ≥ 25 kg/m 2 ).…”
supporting
confidence: 66%
“…Previous systematic reviews with meta-analysis have shown that overweight and obesity increased the risk of LBP [37,38]. Moreover, many of the unhealthy lifestyle factors included in the present study have been considered to be associated with overweight/obesity [23,24,26,28]. Therefore, to eliminate the effects of BMI status on LBP, we analyzed the association of LBP with lifestyle risk according to BMI strata (underweight, normal, and overweight/obesity).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In terms of shift work, previous human epidemiological studies indicated that shift work, especially the duration of shift work, is associated with an increased risk of obesity [26,27]. Regarding the timing of meals, studies showed that skipping the first meal of the day (breakfast) increases the risk of obesity [28,29], that the multivariable-adjusted odds ratio of obesity was even higher with a late dinner and bedtime snack than with skipping breakfast [30], and that subjects given 2000 calories in a single daily meal for a week showed greater body weight loss when this meal was given at breakfast rather than at dinner [31]. Shift work and varying meal timings not only are associated with the increased risk of obesity but also alter the biological rhythm.…”
Section: Circadian Rhythm In Obesitymentioning
confidence: 99%
“…Besides, emerging evidence suggests that the timing of food intake relative to sleep timing behavior could also have a negative impact on BMI [3,11]. For example, cross-sectional studies have reported that eating dinner less than two hours before bedtime is significantly associated with hyperglycemia, and higher odds of being overweight or obese [12,13]. In consonance, Garaulet and colleagues [14] showed that late dining resulted in impaired glucose tolerance, mainly due to concurrence between the postprandial period and endogenous melatonin concentrations.…”
Section: Introductionmentioning
confidence: 99%